Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0256690
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and anxiety symptoms and COVID-19-related factors among men and women in Nigeria

Abstract: Despite the greater adverse economic impacts in low and middle-income (LAMI) compared to high-income countries, fewer studies have investigated the associations between COVID-19-related stressor and mental health in LAMI countries. The objectives of this study were to determine the associations between COVID-19-related stressors and anxiety and depressive symptoms while controlling for known risk and protective factors and to investigate any sex differences. An online survey was carried out to assess sociodemo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 47 publications
(69 reference statements)
4
37
2
Order By: Relevance
“…The high rate of psychological distress found among healthcare workers in the present study is consistent with that found in Nigeria [7], in other low-and-middle-income countries [25] and high-income countries [26]. Our findings that the female subjects experience significantly higher levels of psychological distress is in keeping with previous studies that have explored gender differences in the general population [27], and the distress associated with the untoward experiences in response to the ongoing COVID-19 pandemic [28]. This has been reported among the general population and among populations of health workers in developed and developing countries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high rate of psychological distress found among healthcare workers in the present study is consistent with that found in Nigeria [7], in other low-and-middle-income countries [25] and high-income countries [26]. Our findings that the female subjects experience significantly higher levels of psychological distress is in keeping with previous studies that have explored gender differences in the general population [27], and the distress associated with the untoward experiences in response to the ongoing COVID-19 pandemic [28]. This has been reported among the general population and among populations of health workers in developed and developing countries.…”
Section: Discussionsupporting
confidence: 92%
“…Women tend to experience more psychological distress because of role strain, work balance problems, lack of sufficient support systems, and unique challenges of pregnancy and motherhood [ 29 ]. While men could experience more disruptions than women in some aspects of their life [ 30 ], the overall experience of psychological distress has consistently been more among the women [ 28 ]. This may also reflect the higher vulnerability of women for internalizing problems [ 31 ] while men may be more likely to manifest distress with externalizing problems [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the important predictor of anxiety and depression was S-COVID-19-S. Similarly, previous studies have found that people with S-COVID-19-S had a higher depression likelihood [26,30,60]. In addition, hemodialysis patients who have a family member with suspected or confirmed COVID-19 were more likely to experience anxiety [23].…”
Section: Discussionsupporting
confidence: 83%
“…Each item was scored 0 (No) or 1 (Yes). The instrument had been previously used in Nigeria with a Cronbach's alpha of 0.73 [33]. The Cronbach's alpha in the present study was 0.80.…”
Section: Intimate Partner Violencementioning
confidence: 80%